(untitled) (Research, Society and Development, 2022)
Introduction: Nowadays, depression is one of the most disabling causes worldwide, affecting all people, directly affecting their daily lives such as: work, social relationships, family and others. (Silva et al., 2019). Physical exercise is an important ally in the prevention and treatment of depression, promoting well-being for the patient, aiming at changing daily habits and improving quality of life. (Silva, Vieira, & Brito, 2019) Objective: awareness of the importance of physical exercise in the prevention and treatment of depression. Methodology: Integrative literature review, with a search in SciELO, Lilacs and PubMed databases, collecting works published in Portuguese and English in the last 5 years (2017-2021). Results: 143 articles were found according to the inclusion and exclusion criteria, being used for the discussion only 8. Discussion: The vast majority of articles indicated that physical exercise associated with pharmacological therapy has beneficial effects, although they need research with less risk of bias. Conclusion: Physical exercise should be implemented in the treatment of people diagnosed with depression, being accompanied by a trained professional, it has great chances of obtaining satisfactory results.